2019
DOI: 10.1108/lht-12-2018-0192
|View full text |Cite
|
Sign up to set email alerts
|

Social media, diffusion of innovations, morale and digital inequality

Abstract: Purpose The purpose of this paper is to explore social media usage in an academic library in South Africa and the factors influencing its use. The primary goal of the study was to examine perceptions surrounding the impact of non-adoption of social media on morale, and to explore the consequences of digital inequality. Design/methodology/approach Using a qualitative method, in-depth interviews were conducted with a small sample comprising six key informants at the University of Limpopo Libraries. Findings … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 12 publications
0
17
0
Order By: Relevance
“…It seems that the low speed of the Internet in developing countries is a serious problem for the digital age, as McNicol and Aillerie (2017) underlined digital divide and inequalities in social media usage in these kinds of countries. Additionally, Williams et al (2019) highlighted bridging the digital divide by lifting the ban on social media for users to explore innovative methods of communication and develop their skills. Besides, Williams et al (2019) identified low bandwidth, poor internet connectivity and dated ICT infrastructure as key challenges and barriers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It seems that the low speed of the Internet in developing countries is a serious problem for the digital age, as McNicol and Aillerie (2017) underlined digital divide and inequalities in social media usage in these kinds of countries. Additionally, Williams et al (2019) highlighted bridging the digital divide by lifting the ban on social media for users to explore innovative methods of communication and develop their skills. Besides, Williams et al (2019) identified low bandwidth, poor internet connectivity and dated ICT infrastructure as key challenges and barriers.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Williams et al (2019) highlighted bridging the digital divide by lifting the ban on social media for users to explore innovative methods of communication and develop their skills. Besides, Williams et al (2019) identified low bandwidth, poor internet connectivity and dated ICT infrastructure as key challenges and barriers. Therefore, it is imperative that university officials must resolve this problem, at least for faculty members ASAP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nyahodza and Higgs (2017) indicate that there are two levels of digital divide consist of the global and local digital divide, and with this theory, Williams et. al (2019) conclude that these digital inequalities are caused by financial restraints.…”
Section: Digital Dividementioning
confidence: 98%
“…There is another research conducted to explore social media usage in academic libraries in South Africa, but again the study is focusing on academic libraries only. The study was conducted by Williams et al (2019) and it was focusing on the rural area. On the other hand, Xie and Stevenson (2014) say that general research was completed for digital libraries in North America and Europe to investigate the applications of social media in digital libraries to identify related problems.…”
Section: Literature Reviewmentioning
confidence: 99%